Moving Further on Civil Service Reforms in Ethiopia : Findings and Implications from a Civil Service Survey and Qualitative Analysis - World Bank (World Bank, Washington, DC, 2019)
This report identifies key challenges facing the Ethiopian civil service today and suggests avenuesfor further reforms. Ethiopia’s civil service has so far developed at a rapid pace and faces anumber of constraints, challenges, and new or expanding demands. Continuing reform efforts and building on past achievements is critical for the successful implementation of Ethiopia’s Growth and Transformation Program (GTP II). While the past two decades have seen important achievements made, the government seeks to further strengthen its economic governance and service delivery.The analytic effort that this report reflects was triggered by a request from the Ministry ofPublic Service and Human Resource Development (MPSHRD). The Ministry sought to identify challenges and options to target and pursue further reforms and efforts to strengthen the civil service and its contributions to service delivery. The report is based on several sources: (i) the Ethiopian Civil Servants Survey (ECSS), which was undertaken in June through September 2016 and targeted professional level staff and directors or heads of federal ministries or agencies, regional bureaus, and woreda offices; (ii) a series of key informant interviews with officials and stakeholders, as well as focus group discussions with members of ‘Public Wings’; and (iii) administrative data and information, e.g. concerning the number of civil servants, as wellas salaries and benefits. The focus is on five key service delivery sectors: agriculture, education, health, revenue collection, and trade—all critical areas for state activity. The analysis encompasses an assessment of previous and ongoing reforms, and takes a look at the constraints and overall quality of current management practices. Where possible, the report also compares the civil service in Ethiopia to that of other countries, based on information gathered from similar surveys and other comparative information.